2004
DOI: 10.1037/0735-7044.118.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala and Ventral Hippocampus Contribute Differentially to Mechanisms of Fear and Anxiety.

Abstract: Cytotoxic ventral hippocampal lesions produced anxiolytic effects on 4 ethologically based, unconditioned tests of anxiety in the rat (hyponeophagia, black/white 2-compartment box test, a successive alleys test that represents a modified version of the elevated plus-maze, and a social interaction test). Dorsal hippocampal lesions did not produce anxiolytic effects on these tests, suggesting a distinct specialization of function within the hippocampus. Furthermore, the effects of ventral hippocampal lesions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
245
1
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 336 publications
(270 citation statements)
references
References 93 publications
18
245
1
3
Order By: Relevance
“…Our adult findings accord with prior studies in adult rodents (Crawley, 1981;Crawley & Goodwin, 1980;McHugh, Deacon, Rawlins, & Bannerman, 2004;Ramos, Berton, Mormede, & Chaouloff, 1997). The youngest rats reported with use of the black and white box in the literature are early adolescents (P28 -P32).…”
Section: Discussionsupporting
confidence: 90%
“…Our adult findings accord with prior studies in adult rodents (Crawley, 1981;Crawley & Goodwin, 1980;McHugh, Deacon, Rawlins, & Bannerman, 2004;Ramos, Berton, Mormede, & Chaouloff, 1997). The youngest rats reported with use of the black and white box in the literature are early adolescents (P28 -P32).…”
Section: Discussionsupporting
confidence: 90%
“…Increased expression of NPY (which also has anticonvulsant features; Richichi et al, 2004) in the hippocampus may also help in explaining the slower dentate gyrus kindling rate in betamethasone-exposed immature rats compared to saline-exposed rats in our previous study (Velíšek, 2005b). Earlier studies have shown that mainly ventral but also dorsal hippocampus is involved in anxiety control (Andrews et al, 1997;Bannerman et al, 2002aBannerman et al, , b, 2003Gonzalez et al, 1998;Kjelstrup et al, 2002;McHugh et al, 2004) and NPY alterations in the hippocampus affect anxiety behaviors (Heilig, 2004;Thorsell et al, 2000). We did not see an increase in NPY expression in the basolateral amygdala; however, lesion studies have demonstrated that this region does not participate in the anxiety behavior tested in the elevated plus maze (Gonzalez et al, 1996;Treit et al, 1993), and that the amygdala is rather associated with fear control .…”
Section: Technical Considerationsmentioning
confidence: 62%
“…In previous studies, lesions of the amygdala have failed to alter behavior in the elevated plus maze or other tests of novelty (McHugh et al, 2004;Treit et al, 1993a, b). Similarly, in this set of experiments, lidocaine inactivation of the CeA or BLA did not attenuate the anxiolytic properties of diazepam or baseline anxiety-like behaviors in the plus maze.…”
Section: Discussionmentioning
confidence: 98%
“…Although this is in agreement with other literature, it is at odds with the idea that the anxiolytic actions of these drugs are localized to amygdalar nuclei. Lesion techniques, however, induce permanent destruction of large areas encompassing much of the amygdaloid complex (Treit et al, 1993a, b;McHugh et al, 2004). They also require animals to recover from surgery for several days after the lesion is introduced, potentially allowing for neural adaptations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation